Anthropometric Characteristics in Newborns with a History of Chronic Energy Deficiency (CED) in Pregnancy: A Descriptive Study - Agustina Hariyani, Ririn; Sumantri, Sumantri; Widhi Astuti, KH Endah (Poltekkes Kemenkes Surakarta, 2024)
Background: Chronic energy deficiency (CED) in pregnant women is a nutritional condition characterized by an upper arm circumference (UAC) of less than 23.5 cm, reflecting a long-term deficit in energy and protein intake. CED can increase the risk of low birth weight (LBW) and stunting in infants. Therefore, monitoring the nutritional status of pregnant women is important to prevent infant growth disorders. The objective of this study was to determine the anthropometric characteristics of newborns with a history of CE during pregnancy at the Bayat Community Health Center, Klaten District. Methods: This study used a quantitative descriptive design. The population consisted of all infants with a history of KEK pregnancy at the Bayat Community Health Center from January to December 2021. The sampling technique used total sampling of 112 infants. The research instrument used medical record documentation sheets, and data analysis was performed univariately using frequency distribution. Results: Most infants had normal weight (86.6%), normal length (73.2%), and normal head circumference (93.8%). Maternal characteristics showed that the majority were aged 20–35 years (91.1%), had a high school education (55.4%), were unemployed (76.8%), had an interbirth interval of < 2 years (59.8%), were primiparous (52.7%), had Hb levels ≥ 11 g/dl (86.6%), and had mature pregnancies (93.8%). Conclusion: The anthropometric measurements of newborns tended to be normal and were related to maternal characteristics, especially birth interval ≥ 2 years, which had the highest proportion of babies with normal weight (81.3%), length (67.9%), and head circumference (79.5%). It is recommended that health workers increase monitoring of nutrition in pregnant women with KEK and educate them on the ideal birth interval to support optimal infant growth and development.